Support to Nigeria's National Biosafety Guideline on Gene Editing - CGIAR Research Program on Policies, Institutions, and Markets (2021)
In 2020, Nigeria became the first African country to issue gene editing guidelines, which ensure that gene editing products don't have adverse impacts on human health or the environment.